2002
DOI: 10.1530/eje.0.1470733
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR provides evidence for thyrotropin receptor mRNA expression in orbital as well as in extraorbital tissues

Abstract: Objective: The TSH receptor (TSHr) expressed on thyroid follicular cells is the autoantigen involved in the pathogenesis of Graves' hyperthyroidism. Whether this receptor is expressed in extrathyroidal tissues, and whether it participates directly in the pathogenesis of thyroid-associated ophthalmopathy (TAO) is unclear. Design: The aim of the present study was to measure TSHr mRNA in retro-orbital tissues, retro-orbital adipose tissue, extraocular muscle, and skin from patients with TAO and in several tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 22 publications
0
27
1
Order By: Relevance
“…A TSHr variant transcript comprising essentially exons 1 -8 was also described in many locations, including ocular muscle, fat, lymphocytes and fibroblasts (11). Recently, we have detected by real-time PCR similar levels of TSHr mRNA in TAO orbital tissues and extraorbital tissues from patients not affected by thyroid diseases (12). The expression and function of the TSHr in cultured rat preadipocytes are closely related to cellular differentiation (13), so fibroblasts of the human connective orbital tissue may be important in the development of TAO not only because they are the major source of glycosaminoglycans, but also because the are able to differentiate into mature adipocytes and increase the expression of a functional TSHr, the hypothetical common antigen in thyroid gland and retro-ocular tissue (14,15).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…A TSHr variant transcript comprising essentially exons 1 -8 was also described in many locations, including ocular muscle, fat, lymphocytes and fibroblasts (11). Recently, we have detected by real-time PCR similar levels of TSHr mRNA in TAO orbital tissues and extraorbital tissues from patients not affected by thyroid diseases (12). The expression and function of the TSHr in cultured rat preadipocytes are closely related to cellular differentiation (13), so fibroblasts of the human connective orbital tissue may be important in the development of TAO not only because they are the major source of glycosaminoglycans, but also because the are able to differentiate into mature adipocytes and increase the expression of a functional TSHr, the hypothetical common antigen in thyroid gland and retro-ocular tissue (14,15).…”
Section: Introductionmentioning
confidence: 71%
“…The nucleotide sequence of the primers and probes (Applied Biosystems) are shown in Table 1. Quantitative PCR reactions were carried out on 96-well optical reaction plates using a cDNA equivalent of 50 ng total RNA for each sample in a volume of 50 ml using the TaqMan Universal PCR Master Mix (Applied Biosystems) as described previously (12). To minimize errors arising from variations in the amount of starting RNA among samples, amplification of b-actin mRNA was performed as an internal reference against which other RNA values can be normalized.…”
Section: Determination Of Tshr Mrna Levels Using Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Non as in endothelial cells obtained from the human aorta [14][15][16][17]. Studies performed in a rat model of thyroid goitrogenesis found that TSH treatment increases thyroid capillary density [18].…”
Section: Pe or Gh Groupmentioning
confidence: 99%
“…Stimulation of the TSHR via TSH on thyroid cells leads to production of the thyroid hormones (THs), tri-iodothyronine (T 3 ) and thyroxine (T 4 ) (Toccafondi et al 1982). The TSHR expression by other tissue cells has also been reported (Haraguchi et al 1996, Hoermann 1996, Dutton et al 1997, Bell et al 2000, Agretti et al 2002, Tsai et al 2004, Ellerhorst et al 2006. However, exact function of its expression in extrathyroidal tissues has not been clarified.…”
Section: Introductionmentioning
confidence: 99%